Writing the nation in Reformation England, 1530-1580 - Shrank, Cathy (Oxford University Press, 2006)
'Writing the Nation in Reformation England' is a unique study of a neglected period of English writing. It places mid-Tudor literature (1530-1580) within the context of important debates about English nationhood, the nature of the English Reformation and English humanism.